2022
DOI: 10.3390/nano12030489
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Modified Magnetite-Based Nanocomposites Used for Wastewater Treatment and Evaluated on Zebrafish (Danio rerio) Model

Abstract: Magnetite-based nanocomposites are used for biomedical, industrial, and environmental applications. In this study, we evaluated their effects on survival, malformation, reproduction, and behavior in a zebrafish animal model. Nanoparticles were synthesized by chemical coprecipitation and were surface-functionalized with (3-aminopropyl) triethoxysilane (APTES), L-cysteine (Cys), and 3-(triethoxysilyl) propylsuccinic anhydride (CAS). All these nanocomposites were designed for the treatment of wastewater. Zebrafis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Ocular and body coloration, somite development, tail detachment, heart rate, and blood circulation in the treated embryos did not change significantly from the untreated control. These findings show that none of the four concentrations tested for the benzimidazole derivatives under consideration produced embryo toxicity harm to zebrafish larvae [40] . The result of 96 hpf survival rates revealed that the compounds ( 3a , 3b , 3f , 3i , 3l , 3h , and 1a ) were significantly more hazardous to the embryos than ( 3c – e , 3g , and 3I‐k ).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Ocular and body coloration, somite development, tail detachment, heart rate, and blood circulation in the treated embryos did not change significantly from the untreated control. These findings show that none of the four concentrations tested for the benzimidazole derivatives under consideration produced embryo toxicity harm to zebrafish larvae [40] . The result of 96 hpf survival rates revealed that the compounds ( 3a , 3b , 3f , 3i , 3l , 3h , and 1a ) were significantly more hazardous to the embryos than ( 3c – e , 3g , and 3I‐k ).…”
Section: Resultsmentioning
confidence: 84%
“…These findings show that none of the four concentrations tested for the benzimidazole derivatives under consideration produced embryo toxicity harm to zebrafish larvae. [40] The result of 96 hpf survival rates revealed that the compounds (3a, 3b, 3f, 3i, 3l, 3h, and 1a) were significantly more hazardous to the embryos than (3c-e, 3g, and 3I-k). Furthermore, the toxicity of the benzimidazole derivatives used in treatment with various concentrations.…”
Section: S No Compoundsmentioning
confidence: 97%
“…Hu et al 78 observed that exposure to a nanocomposite affected the mortality rate and hatching rate of zebrafish embryos in dose- and time-dependent ways. 78 In zebrafish embryos, the toxicities of many other nanomaterials, such as nanocomposite nanoparticles, including ZnO NPs, 58 TiO 2 NPs, 79 copper NPs, 80 CuO NPs, 81 ZrO NPs, 82 SiO 2 NPs 83 and carbon nanotubes, 84 and magnetite based nanocomposites, 85 have been examined. Significant results include higher mortality, a lower hatching rate, and developmental abnormalities.…”
Section: Resultsmentioning
confidence: 99%
“…FTIR was carried out to confirm the immobilization of laccase on magnetite nanoparticles (laccase-magnetite) ( Figure 2 ). Bare magnetite exhibited two bands at 1620 and 3160 cm −1 related to the vibration of the hydroxyl groups on the surface of the magnetite ν (Fe-OH) [ 39 , 40 ]. Laccase-magnetite nanobiocomposites presented a peak at 3350 cm −1 attributed to the NH stretching vibration of laccase amines and a peak at 1080 cm −1 characteristic of the Si-O-Si bond resulting after silanization [ 39 ].…”
Section: Resultsmentioning
confidence: 99%